Perinatal exposure to endocrine disrupting chemicals and neurodevelopment: How articles of daily use influence the development of our children. Issue 5 (September 2021) - O'Shaughnessy, Katherine L.; Fischer, Florence; Zenclussen, Ana C.
Abstract : Substances that interfere with the body's hormonal balance or their function are called endocrine disrupting chemicals (EDCs). Many EDCs are ubiquitous in the environment and are an unavoidable aspect of daily life, including during early embryogenesis. Developmental exposure to these chemicals is of critical relevance, as EDCs can permanently alter developmental programs, including those that pattern and wire the brain. Of emerging interest is how these chemicals may also affect the immune response, given the cross-talk between the endocrine and immune systems. As brain development is strongly dependent on hormones including thyroid, androgens, and estrogens, and can also be affected by immunomodulation, this complicated interplay may have long-lasting neurodevelopmental consequences. This review focuses on data available from human cohorts, in vivo models, and in vitro assays regarding the impact of EDCs after a gestational and/or lactational exposure, and how they may impact the immune system and/or neurodevelopment.